Juvenile delinquency and justice in contemporary China: a critical review of the literature over 15 years - Zhang, Lening (Crime, law and social change, 2008)
The study reviews research on juvenile delinquency and justice in China since 1990. The review covers three issues that have been studied in the publications: (1) the nature and scope of China’s juvenile delinquency; (2) individual, group, and institutional factors and their roles in delinquency involvement; and (3) the development of China’s juvenile justice. Because Hong Kong is a special region of China and has a different social, political, and legal system, the study reviews the publications on Hong Kong’s juvenile delinquency and justice in a separate section. It summarizes the findings derived from the review, analyzes and discusses the limitations of the reviewed studies, and provides prospects for future research in the area.